Special Issue of the Manufacturing Engineering Society (MES) - Rubio, Eva M.; Camacho, Ana M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book derives from the Special Issue of the Manufacturing Engineering Society (MES) that was launched as a Special Issue of the journal Materials. The 48 contributions, published in this book, explore the evolution of traditional manufacturing models toward the new requirements of the Manufacturing Industry 4.0 and present cutting-edge advances in the field of Manufacturing Engineering focusing on additive manufacturing and 3D printing, advances and innovations in manufacturing processes, sustainable and green manufacturing, manufacturing systems (machines, equipment and tooling), metrology and quality in manufacturing, Industry 4.0, product lifecycle management (PLM) technologies, and production planning and risks.